The The Influence of Consumer Online Ratings and Reviews on Purchase Decisions on Tiktok Shop Marketplace Users - Sari, Dewi Puspita; Era, Agustina Yamini (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2023)
Background: At this time shopping through the marketplace is a common thing, in addition to making it easy, consumers are also faced with many choices and a lot of different information from the seller. Consumers cannot touch and feel the product. This often raises doubts in the minds of consumers, so it takes effort to build consumer trust. Therefore, consumers try to obtain information through reviews and ratings available on various online platforms. Objective: This study aims to examine the influence of consumer online ratings and reviews on purchasing decisions on Tiktok Shop marketplace users. Research Method: This research using the quantitative as the method with data collection techniques through the distribution of questionnaires to people in the Special Region of Yogyakarta who have made online transactions on the TikTok shop marketplace totaling 184 respondents. The sampling procedure used in this study was non-probability with purposive sampling technique. Research Results: The results obtained after data analysis on Consumer Online Rating have a significant influence on purchasing decisions. Review has a significant positive influence on purchasing decisions. And simultaneously Consumer Online Ratings and Reviews have a positive and significant influence on purchasing decisions. This is in accordance with what was hypothesized.